Behold an Animal : Four Exorbitant Readings - Ravindranathan, Thangam (Book collections on Project MUSE., 2020)
"Behold an Animal examines the philosophical significance of animals in the French novel today. It contributes to critical scholarship on contemporary French literature, comparative literature, Derrida and Deleuze studies, and animal studies"--